Role of CaCO3 alone and CaCO3 plus Vitamin D3 in terms of Calcium Phosphorus Product in Chronic Kidney Diseases - Adhikary, L; Acharya, S; Acharya, L (Journal of Nepal Health Research Council, 2011)
Background: CaCO3 alone and CaCO3 plus vitamin D3 metabolites are commonly prescribed in CKD patients. The objective of this study is to analyze the changes in Ca x P product, calcium level and phosphorus level in CKD patients receiving calcium carbonate alone and calcium carbonate with vitamin D3 in combination. Methods: A prospective, cross sectionalstudy among CKD patients under maintenance hemodialysis two times a week were studied over a period of one year. The patients were divided into two groups receiving oral CaCO3 alone and CaCO3 plus vitamin D3 once a day. The patients were followed for 1 month and result of Ca x P product was analyzed accordingly. Results: Mean decrease of Ca x P product in CaCO3 group is (50.42+/-8.85 to 47 +/-6.63) in one month, p value =0.001(0.6-5) and CI- 95%. There is also significant reduction of phosphorus level in CaCO3 group than CaCO3 plus vitamin D3 group. Mean decrease in phosphorus in CaCO3 group is (5.51+/-0.76 to 5.17+/- 0.05) in one month. P value =0.01(0.14-0.53) and CI 95%. Conclusions: There is a significant decrease in Ca x P product and phosphorus level was observed in CKD patients taking CaCO3 alone. Keywords: calcium carbonate, calcium phosphorus product, chronic kidney disease, vitamin.